Spirituality of Green Purchase Behavior : Does Religious Segmentation Matter? - Md Harizan, Siti Haslina; Abdul Rahman, Wan Afezah Wan (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
The current decade of the 21st century has witnessed the global warming phenomenon caused by massive greenhouse gas (GHG) emissions rooted mainly from unsustainable consumption behaviour. As part of environmentally significant behaviour, the act of acquiring green or environmentally-friendly products was deemed important. Since consumers in the 21st century can be associated with a creative generation which constantly seeks to improve themselves and the world, it is therefore an attempt of this paper to investigate the influences of spirituality on willingness to purchase green products. The study also attempts to seek differences between Muslims and non-Muslims in Malaysia according to their level of spirituality and willingness to purchase green products. Data was collected via survey using self-reported questionnaires among consumers intercepted at several outlets in the central region of Peninsular Malaysia. A total of 606 usable questionnaires were finally elicited among Malaysian individual consumers. The findings indicated that spirituality has a significant influence on willingness to purchase green products. Malaysian Muslims make a difference only in spirituality while there is no difference found in terms of willingness to purchase green products. Theoretically, the findings had extended the notion of value orientation in the value-belief-norm theory by demonstrating the significant influences of spirituality dimensions on willingness to purchase green products. The implications of the study too, may benefit further policy planning and promotional campaign formulation by the government, non-government organisations, business owners, marketers, religious institutions, media and other related institutions.